The First World War and the End of the Habsburg Monarchy, 1914-1918 - Rauchensteiner, Manfried (2014)
The origins of World War I were different and varied. But it was Austria-Hungary which unleashed the war. After more than four years the Habsburg Monarchy was defeated and ended as a failed state.